The Role of Artificial Intelligence in Enhancing Learning in the Era of Society 5.0 - Sahat Renol HS; Selvita Eka Eviana Purba (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
The Society 5.0 era marks the integration of intelligent technologies into human life, including the field of education. Artificial Intelligence (AI) has emerged as a key innovation driving the transformation of learning systems. This study aims to analyze the role of AI in enhancing the quality of education through a literature review. Sources utilized include journals, scientific articles, and recent reports from both domestic and international contexts. The findings indicate that AI can personalize learning experiences, accelerate assessment processes, and broaden educational access through adaptive platforms, educational chatbots, and learning analytics systems. AI implementation has proven effective across various educational levels, from elementary schools to higher education institutions. However, challenges such as digital infrastructure gaps, low technological literacy among educators, and ethical and data privacy concerns require serious attention. Within the Society 5.0 framework, AI functions as a transformative agent supporting data-driven learning and competency development. To optimize AI utilization, progressive policies, educator training, and stakeholder collaboration are essential. With an appropriate approach, AI can serve as a strategic partner in advancing education in the Society 5.0 era.